2002
DOI: 10.1086/338236
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity of DNA Amplification Testing for the Detection of Pharyngeal Gonorrhea in Men Who Have Sex with Men

Abstract: We compared ligase chain reaction (LCR) assay with standard culture for the detection of pharyngeal Neisseria gonorrhoeae infection in men who have sex with men (MSM) presenting at a sexually transmitted diseases clinic in San Francisco. Pharyngeal specimens were obtained from 200 MSM who reported performing fellatio during the previous 2 weeks. Confirmatory testing of discrepant specimens was conducted using N. gonorrhoeae pilin proteins. Prevalence of pharyngeal N. gonorrhoeae was 6% by culture or 11% by LCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 28 publications
5
38
0
2
Order By: Relevance
“…Ligase chain reaction (LCR) testing has indicated that the true incidence of pharyngeal and rectal gonorrhea in MSM may be double that detected by bacterial culture, suggesting that the sensitivity of bacterial culture may be as low as 50% for these specimen sites. 43,78,79 These results are supported by a more recent study using an N. gonorrhoeae porA pseudogene PCR assay. 80 The lower sensitivity of bacterial culture in the extragenital sites may be attributed to the heavy colonization of these sites by a broad range of other organisms, including other Neisseria species, which may interfere with N. gonorrhoeae isolation.…”
Section: Diagnosis Of Pharyngeal and Rectal Gonorrheasupporting
confidence: 65%
See 1 more Smart Citation
“…Ligase chain reaction (LCR) testing has indicated that the true incidence of pharyngeal and rectal gonorrhea in MSM may be double that detected by bacterial culture, suggesting that the sensitivity of bacterial culture may be as low as 50% for these specimen sites. 43,78,79 These results are supported by a more recent study using an N. gonorrhoeae porA pseudogene PCR assay. 80 The lower sensitivity of bacterial culture in the extragenital sites may be attributed to the heavy colonization of these sites by a broad range of other organisms, including other Neisseria species, which may interfere with N. gonorrhoeae isolation.…”
Section: Diagnosis Of Pharyngeal and Rectal Gonorrheasupporting
confidence: 65%
“…Even the Abbott LCx assay, which was shown to be highly specific by Palmer et al, 49 has provided false-positive results in these samples. Young et al 43 found that the positive predictive value of the LCR was 94.1% for rectal swabs and 88.9% for pharyngeal swabs in a population of MSM, and similar results were reported by Page-Shafer et al 78 In both of these studies, the incidence of N. gonorrhoeae was approximately 10%. Consequently, the positive predictive value of the LCR may be considerably less if a low incidence population were tested.…”
Section: Diagnosis Of Pharyngeal and Rectal Gonorrheasupporting
confidence: 64%
“…NAATs have been shown to be significantly more sensitive than culture in the detection of chlamydia and gonorrhoea, particularly in extra-genital sites (103)(104)(105)(106)(107)(108). Owing to cross-reactivity with nongonorrhoea Neisseria species, all NAAT tests for gonorrhoea from all sites should be confirmed with supplementary tests to improve specificity (109)(110)(111).…”
Section: Chlamydia and Gonorrhoeamentioning
confidence: 99%
“…This poses a problem for the specificity of DNA-based diagnostic tests for N. gonorrhoeae, since the detection of a single gonococcus-specific gene that has been acquired by a commensal Neisseria isolate would result in a false-positive laboratory diagnosis. Assays of the highest specificity are required for testing extragenital specimens, in particular pharyngeal specimens, because this site commonly harbors commensal Neisseria and/or Neisseria meningitidis (11, 16).Commercial molecular diagnostic tests for N. gonorrhoeae are designed for use on genital swabs and urine specimens, but some have also been evaluated for their use on extragenital specimens, such as pharyngeal and rectal swabs (17,18,21; H. Young, A. Moyes, and A. McMillan, Abstr. 12th Meet.…”
mentioning
confidence: 99%